(untitled) - Rheingold, Howard (New York, 1991)
Imagine being able to "walk" into your computer and interact with any program you create. It sounds like science fiction, but it's science fact. Surgeons now rehearse operations on computer-generated "virtual" patients, and architects "walk through" virtual buildings while the actual structures are still in blueprints. In Virtual Reality, Howard Rheingold takes us to the front lines of this revolutionary new technology that creates computer-generated worlds complete with the sensations of touch and motion, and explores its impact on everything from entertainment to particle physics.
Keywords: Thực tế ảo,Khoa học,Science,Virtual reality; Trình mô phỏng,Computer simulation